2018
DOI: 10.3166/rea-2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome d’hyperviscosité : mise au point pour les réanimateurs

Abstract: Le syndrome d’hyperviscosité (SH) est une entité clinique composée de signes variables non spécifiques et dont le diagnostic repose sur un faisceau d’arguments contextuels, anamnestiques et clinicobiologiques. En dehors de la mesure de la viscosité plasmatique, l’examen le plus spécifique pour confirmer le diagnostic semble être le fond d’œil. L’incidence du SH est inconnue, mais il s’agit d’une complication rare d’un grand nombre de pathologies. La physiopathologie est en rapport avec une augmentation de la v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is suggested that local factors such as anatomical vascular retinal arrangement or high intraocular pressure would contribute to retinal hemorrhage development. 19 Soman et al noticed that the hemoglobin level improvement from 5 to 7 g/dL reduced the risk of having sub-hyaloid hemorrhages, and maintaining platelet counts above 50,000 cells/mm 3 decreased the risk of ophthalmic manifestations. 2 In our paper, adults were more likely to have leukemic retinopathy than children.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that local factors such as anatomical vascular retinal arrangement or high intraocular pressure would contribute to retinal hemorrhage development. 19 Soman et al noticed that the hemoglobin level improvement from 5 to 7 g/dL reduced the risk of having sub-hyaloid hemorrhages, and maintaining platelet counts above 50,000 cells/mm 3 decreased the risk of ophthalmic manifestations. 2 In our paper, adults were more likely to have leukemic retinopathy than children.…”
Section: Discussionmentioning
confidence: 99%